2011
DOI: 10.1016/s0140-6736(11)60613-2
|View full text |Cite
|
Sign up to set email alerts
|

Addition of cetuximab to oxaliplatin-based first-line combination chemotherapy for treatment of advanced colorectal cancer: results of the randomised phase 3 MRC COIN trial

Abstract: SummaryBackgroundIn the Medical Research Council (MRC) COIN trial, the epidermal growth factor receptor (EGFR)-targeted antibody cetuximab was added to standard chemotherapy in first-line treatment of advanced colorectal cancer with the aim of assessing effect on overall survival.MethodsIn this randomised controlled trial, patients who were fit for but had not received previous chemotherapy for advanced colorectal cancer were randomly assigned to oxaliplatin and fluoropyrimidine chemotherapy (arm A), the same … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

23
638
2
19

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 869 publications
(682 citation statements)
references
References 22 publications
23
638
2
19
Order By: Relevance
“…Individual patient data were obtained from selected arms of three large randomised trials (FOCUS [ISRCTN 79877428], [13] COIN [ISRCTN 27286448], [14,15] PICCOLO [ISRCTN 93248876] [16,17] to reflect different clinical uses of standard cytotoxic chemotherapy (without targeted therapy) in aCRC (Supplementary Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Individual patient data were obtained from selected arms of three large randomised trials (FOCUS [ISRCTN 79877428], [13] COIN [ISRCTN 27286448], [14,15] PICCOLO [ISRCTN 93248876] [16,17] to reflect different clinical uses of standard cytotoxic chemotherapy (without targeted therapy) in aCRC (Supplementary Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…RAS mutations represent the only, molecular, predictive biomarker approved for clinical use, while their prognostic role is still debated. Several randomized studies have shown no significant survival differences between KRAS mutated and KRAS wild-type, CRC patients, independently of anti-EGFR therapy (Price et al, 2011;Hecht et al, 2009;Kastrinakis et al, 1995;Russo et al, 1998;Tol et al, 2010), while others have demonstrated a prognostic role of KRAS in advanced disease (Richman et al, 2009;Maughan et al, 2011;Tejpar et al, 2012). BRAF mutations have been described in about 10% of primary CRC, representing a well-known negative prognostic factor, associated with worse survival outcomes, regardless of any treatment received (Ahn et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The oral TKIs gefitinib and erlotinib have been applied most and currently, they are use in particular for palliative therapy of non-small cell lung cancer [27]. Monoclonal antibodies against EGFR extracellular receptor domain are another group; among these, cetuximab and panitumumab have been used most, predominantly in the therapy of metastatic colorectal cancer [28][29][30][31][32][33]. With the development of molecular biology revealed that the K-RAS oncogene status, and later the entire RAS complex, was a principal predictive factor for the use of anti-EGFR therapy in metastatic colorectal cancer [29,34].…”
Section: Discussionmentioning
confidence: 99%